ASSESSMENT TOOLS FOR ASSESSING COGNITIVE FUNCTIONS OF ELDERLY - Tomagová, Martina (Profese Online, 2009)
This article presents theoretical study concerns with assessment tools cognitive functions of elderly. It offers summary of tools for assessment of cognitive functions of elderly in nursing research and practice. It analyzes common tools as MMSE (Mini-Mental State Examination) and SPMSQ (Short Portable Mental Status Questionnaire).
Keywords: olders; cognitive impairment; diagnosing; assessment tools; MMSE; SPMSQ